Applying health communications to mental illness stigma change. Issue 2 (15th June 2015) - Michaels, Patrick J.; Kosyluk, Kristin; Butler, Ellen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Advocates and researchers have made mental illness stigma elimination a public health priority. Research on stigma change strategies has highlighted programmatic delivery strengths; however, an area in need of further development is in messaging capable of attaining specific behavior change. The paper aims to discuss these issues. Design/methodology/approach – Change goals were incorporated into an existing model of stigma change to propose the TLC4 model (Targeted, Local, Credible, Continuous, Contact, Change Goals). This paper reviews health communications literature regarding tailored messaging, applying these principles to stigma change programs to enhance behavioral impact. Findings – Tailored messages comprises four elements: capturing and maintaining attention, actively thinking about information, having emotional appeal, and making material relevant to each person. Incorporation of these elements enhances the likelihood of an individual making a behavior change. Originality/value – This review can guide facilitators of stigma change programs to craft presentations with tailored messages in directive call-to-actions. Future directions for evaluation of message and behavioral change impact are discussed.